‘A brilliancy of their own’: Female art, beauty and sexuality in Charlotte Brontë’s Jane Eyre - Ioannou, Maria (My University, 2018)
This article studies the portraits of Rosamond Oliver and Blanche Ingram in Charlotte Brontë’s Jane Eyre, to argue that, first, the portraits participate in the nineteenth-century dialogue about women in art and, second, capture Jane’s convictions on the theme of sexual love. This is especially so in the case of Rosamond’s miniature, which comes at a point where Jane has resolved to choose a sexual union rather than a loveless marriage. In an important sense, Jane is Rosamond; the subject (artist) identifies with the object (model) in an equation of female beauty with agency and capacity for sexual feeling.
Keywords: Αrt; Beauty; Female sexuality; Gender; Jane Eyre; Victorian periodicals